Studies on Arylhydrazones, Part-XIV: Reduction of Diethyl Mesoxalate-o-Nitrophenylhydrazone - Prasad, Nagenra; Sahay, Anup; Singh, K.R.K. (Asian Journal of Chemistry, 2010)
The present communication deals with the characterisation ofthe product obtained by the reduction (using various reducing agentssuch as FeSO4/NH3, NH4Cl /Zn dust, Sn/HCl, SnCl2/HCl, H2S/alcoholic NH3 and Na2S2O4) of diethyl mesoxalate-o-nitrophenylhydrazone.Contrary to our expectation the amino compound wasisolated in varying yields along with various side products. In allthe above methods of reduction, the reduction with Na2S2O4 wasproved to be an efficient and excellent method due to easier process,a much better yield of amino compound in spite of the formationof the sodium salt of o-sulphamic acid to a greater extent. Thecharacterisation of o-aminophenylhydrazones obtained in all theabove cases has been done during the present course of investigationon the basis of elemental and spectral studies .. Finally, the aminocompound was established by forming the various derivatives fromthe sodium salt of o-sulphamic acid e.g. N-formyl, N-acetyl,N-benwyl, N-phthaloyl and the various condensation procucts withdifferent aldehydes, the intentity of which was confirmed byelemental and spectral analysis.